Babymouse. [6], Camp Babymouse - Holm, Jennifer L.; Holm, Matthew (New York : Random House, 2007)
Baby Mouse is excited to be going to Camp Wild Whiskers for two weeks, but she soon discovers that camping is not as easy as it seems.
3.7
3-6.
3-6
Keywords: Animals -- Fiction; Camps -- Fiction; Cartoons and comics; Mice -- Fiction; Animals -- Fiction; Camps -- Fiction; Comic books, strips, etc; Mice -- Fiction; Graphic novels